Rural art teachers' access: one museum's online art curriculum. (2nd April 2020) - Beck, D.; Warren, S.
ABSTRACT: Many K-12 schools in the United States face reduced time for the arts due to the time needed to prepare students for high-stakes standardized exams. Although there are advanced placement exams in art history, many rural districts lack the resources to support those efforts. Without the ability to visit large city museums, students lack access to the artworks needed to engage in high-level discussion for substantive arts literacy. This can put children behind in terms of preparation for future employment in graphic arts, digital art production, and related professions. One attempt to overcome this problem was a U.S. art museum's online art curriculum. This article reports an evaluation of the effectiveness of the digital tools developed to support the art courses based on teacher reports of their experiences during a second-year pilot program. We interviewed 12 teachers during the second semester of the pilot implementation. Teachers noted technical problems that hindered curriculum implementation into their art classrooms. Finally, we discuss these challenges' effects resulting from a failure mode and effects analysis and make improvement recommendations focused on improving early-stage developmental analysis, technology stability, products' usability, and tool alignment to pedagogical modes and outcomes for both rural and broader audiences.